Quantifying the effects of food management routines on household food waste. (10th March 2023) - Ananda, Jayanath; Karunasena, Gamithri Gayana; Kansal, Monika; Mitsis, Ann; Pearson, David
Abstract: The aim of this paper is to explore the impact of household food management routines on the amount of food waste. We build on past studies, many of which have used the theory of planned behavior to explain food waste, by incorporating actual food waste. The repetitive and routinised nature of diverse food management routines in the household leads to formation of habits, many of which play a major role in determining the amount of food waste. Using a large national level dataset ( n  = 4324), this paper applies a Partial Least Square - Structural Equation Modelling framework to quantify the influence of food management routines on household food waste. Findings indicate that motivation and norms have a positive and statistically significant (at 1% level) influence on food planning behaviours which in turn contribute to reducing food waste. They also positively influence food storing behaviours. These results are useful for improving effectiveness of household food waste prevention interventions. The impact from highlighting social norms (such as saving planet, easing guilt, and doing the right thing) and motivation (such as saving time, money and educating children) will be enhanced when supported by complementary food management routines in the areas of planning (meal schedule and check stocks before shopping) and storing (extending product life by efficient storage in containers and/or fridge and freezer). Graphical abstract: Image 1 Highlights: Household food management routines influence food waste generation. Understanding complex food management routine are pivotal to reduce food waste. Better food planning and storing significantly reduces food waste. Food disposal showed a positive effect on food waste generation. Social norms and motivations are important in household food planning.